2021
DOI: 10.1055/s-0041-1731634
|View full text |Cite
|
Sign up to set email alerts
|

Synovial Sarcoma of Ethmoidal Sinus

Abstract: Background Synovial sarcoma is an aggressive soft tissue cancer of extremities mainly and rare in head and neck region, whereas rarest in ethmoidal sinus as only three cases have been reported till date. Case Reports We managed two cases of synovial sarcoma who presented with nasal obstruction, epistaxis, and swelling around the nasofacial region. Endoscopic nasal biopsy and immunohistochemistry markers confirmed synovial sarcoma in both the cases. While one case was managed by surgery and chemoradia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
1
0
2
Order By: Relevance
“…In such cases where surgical option is limited, chemotherapy can be used to decrease the tumor size and make the overall therapy more effective, as shown in the case (Saito et al, 2018) in Table 3. However, the effect of chemotherapy is still very unclear due to lack of data and research (Dhiman et al, 2021). More research should be carried out concerning the effect of chemotherapy on SS.…”
Section: Discussionmentioning
confidence: 99%
“…In such cases where surgical option is limited, chemotherapy can be used to decrease the tumor size and make the overall therapy more effective, as shown in the case (Saito et al, 2018) in Table 3. However, the effect of chemotherapy is still very unclear due to lack of data and research (Dhiman et al, 2021). More research should be carried out concerning the effect of chemotherapy on SS.…”
Section: Discussionmentioning
confidence: 99%
“…1 Knowledge about the tumor prognosis is limited; studies showed that the chance of recurrence is high in skull base and paranasal synovial sarcoma. 10 Survival and overall prognosis depend on tumor staging, subtype, combined or single treatment modality, and metastasis. 9 Head and neck sarcomas show a good response to chemotherapy as their behavior in extremities and…”
Section: Case Descriptionmentioning
confidence: 99%
“…Bu beş hastanın üçünde akciğer metastazı gelişirken, bir hastada parotis bezine, bir hastada ise akciğer ve kemik olmak üzere birden çok organda metastaz gelişmiştir. Hastalık nüksüne kadar süre geçen süre medyan 11 aydır (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Nüks eden dokuz hastanın dördü tekrar opere edilirken beşi operasyona uygun bulunmamıştır.…”
Section: Med J Westunclassified
“…Hastalığın 70'den fazla histolojik alt tipi bulunmaktadır (2). Yumuşak doku sarkomları genellikle ekstremiteler veya retroperitonda görülürken %5-10 arasında baş ve boyun bölgesinde görülmektedir (3,4).…”
unclassified